2016
DOI: 10.15405/epsbs.2016.06.44
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Pupils’ Balance Through Rhythmic and Movement Games

Abstract: The increasingly sedentary children's activities (laptop, computer, tablet, video games) have led lately to an alarming number of overweight children. This can affect their posture and balance, which may lead to some gait problems or low success in motor activities. Purpose: The aim of this research was to determine the balance level of elementary school children and provide some physical exercises to improve their coordination. Methods: 60 elementary school children aged 6 to 7 years were selected to particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…All children were screened for posture using the mobile application "PostureScreenMobil", which is widely used for this purpose [16][17][18][19][20][21][22][23].…”
Section: Methodsmentioning
confidence: 99%
“…All children were screened for posture using the mobile application "PostureScreenMobil", which is widely used for this purpose [16][17][18][19][20][21][22][23].…”
Section: Methodsmentioning
confidence: 99%
“…In this research, the objective assessment of balance ability in karate and taekwondo was achieved through the Y-Balance platform ( Figure 01) (Cosma, Rusu, Ilinca, & Nanu, 2016). This is a dynamic test in a leg position that requires strength, flexibility, central control and proprioception, and a position of facial/ forward lying support on one hand.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, several studies have found that poor balance ability is significantly related to an increased risk of ankle injuries in different sports activities, and this relation seems to be more common in males than females. After using games with different equilibrium exercises, over 12 weeks (Cosma, Rusu, Ilinca, & Nanu, 2016), for children aged 6-7 years, changes in the balance of tested subjects demonstrate their influence on the experimental intervention module effectiveness in developing psychomotor skills, the average progress being 32.17% balance on the right foot and 33.16% on the left foot.…”
Section: Problem Statementmentioning
confidence: 99%